MODEL PELATIHAN BERBASIS KINERJA DALAM PENINGKATAN KOMPETENSI TUTOR PENDIDIKAN KESETARAAN - Anan Sutisna & Sutaryat Trisnamasyah (Jurnal Cakrawala Pendidikan, 2010)
Abstract: A Performance-Based Training Model to Improve EquivalenceEducation Tutors Competence. This study aimed to develop a training model toimprove equivalence education tutors competence, employing a performancebasedtraining model, focusing on tutors instructional competence. The trainingmodel was developed based on the fact that the current training process was tooconventional and emphasized the cognitive aspect only. The performance-basedtraining model was developed through research and development. The resultshowed that the performance-based training model was effective to improve theequivalence education tutors pedagogic and andragogic competence in the Centerfor Community Learning Activities.Keywords : performance-based training, equivalence education tutors competencies